Nested or exclusive? The role of identities on blame attribution during the Great Recession. Issue 1 (8th July 2019) - Guinjoan, Marc; Bermúdez, Sandra
Abstract: Despite an increasing number of studies assessing the importance of institutions as regards to accountability, it still remains to be known whether and how an individual's national and regional identity shapes the attribution of responsibilities in multi‐level settings. By focusing on the economic crisis that affected Europe since 2008, we argue that identity‐based assessments of responsibility for the crisis will occur solely among individuals who hold exclusively national or regional identities and who live in regions that have nationalist aspirations. This will be in contrast to individuals that have exclusively identities who live in regions that lack nationalist aspirations, as well as dual‐identity individuals, irrespective of where they live. We test our arguments by using data from Catalonia and Madrid (Spain) and Bavaria and Lower Saxony (Germany). In line with our expectations, our results show that, in minority nationalist regions such as Catalonia, an individual's identity will crucially determine which level of government is blamed for the economic crisis, while this will not occur in regions with no nationalist aspirations. The article reveals the existence of an additional determinant of blame attribution in some specific multi‐level arrangements and contributes to the understanding of the tensions between identity politics and blame avoidance.